1995
DOI: 10.1111/j.1467-9507.1995.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

The social worlds of 8‐ and 12‐month‐old infants: Early experiences in two subcultural contexts

Abstract: In this study, we explored the everyday experiences of 40 infants from families who migrated recently from Central America to the US. Another 42 infants from middle class families of Euro-American background were included to facilitate the evaluation of our methodology and findings. Detailed descriptions of the previous 24 hours were obtained by interviewing the mothers when their infants were 8 and 12 months of age. The infants' experiences and activities were very similar in both groups, and the effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…In addition, despite Ainsworth's careful efforts to operationalize the concept of sensitivity, several researchers have suggested that observer judgments regarding the "appropriateness" of maternal responses are based in part on cultural and other contextual factors, and have recommended adding measures of a variety of maternal and contextual variables (level of social support, personal attachment history/integration, cultural beliefs about parenting and child development) to investigations of the caregiving antecedents of attachment quality (Barnett, Kidwell, & Leung, 1998;De Wolff & van IJzendoorn, 1997;Fisher, Jackson, & Villarruel, 1998;Harwood, Miller, & Irizarry, 1995;Jackson, 1986;Leyendecker, Lamb, Schölmerich, & Fracasso, 1995;Rothbaum, Weisz, Pott, Miyake, & Morelli, 2000;Waters, Bailey, Pederson, & Moran, 1999). Indeed, Ainsworth's meticulous naturalistic studies in Uganda led her to caution future researchers that caregiving must be understood in cultural and historic context (Ainsworth, 1967).…”
Section: Attachment and Maternal Sensitivitymentioning
confidence: 99%
“…In addition, despite Ainsworth's careful efforts to operationalize the concept of sensitivity, several researchers have suggested that observer judgments regarding the "appropriateness" of maternal responses are based in part on cultural and other contextual factors, and have recommended adding measures of a variety of maternal and contextual variables (level of social support, personal attachment history/integration, cultural beliefs about parenting and child development) to investigations of the caregiving antecedents of attachment quality (Barnett, Kidwell, & Leung, 1998;De Wolff & van IJzendoorn, 1997;Fisher, Jackson, & Villarruel, 1998;Harwood, Miller, & Irizarry, 1995;Jackson, 1986;Leyendecker, Lamb, Schölmerich, & Fracasso, 1995;Rothbaum, Weisz, Pott, Miyake, & Morelli, 2000;Waters, Bailey, Pederson, & Moran, 1999). Indeed, Ainsworth's meticulous naturalistic studies in Uganda led her to caution future researchers that caregiving must be understood in cultural and historic context (Ainsworth, 1967).…”
Section: Attachment and Maternal Sensitivitymentioning
confidence: 99%
“…For the social contexts, several studies have found that Latino children are more likely to spend time with relatives rather than with family friends and peers, and that their families' social networks are more likely to be comprised of relatives when compared to their European-American counterparts (Feng, Harwood, Leyendecker, & Miller, 2001;Garcia, 1993;MacPhee, Fritz, & Miller-Heyl, 1996;Miller-Loncar, Erwin, Landry, Smith, & Swank, 1998;Schaffer & Wagner, 1996;Zambrana, Silva-Palacios, & Powell, 1992). In contrast, European-American children are more likely to spend time alone with their mothers (Leyendecker, Lamb, Schölmerich, & Fracasso, 1995).…”
Section: Cultural Differences In Everyday Routinesmentioning
confidence: 92%
“…Because recall data seems most reliable when restricted to a 24-hour period (Juster, 1985), we limited ourselves to this time frame. We also limited our focus to broad descriptions of ongoing activities and to the identification of those present in order to ensure the reliability of this data (Lewis, 1987;Leyendecker et al, 1995;Parke & Tinsley, 1987;Pleck, 1983). Time diaries are effective for obtaining estimates of time use and assessing children's performance versus non-performance of general activities, as well as the presence of other people (Leyendecker, 1993;Leyendecker et al, 1995;Pleck, 1983).…”
Section: Time Diariesmentioning
confidence: 99%
“…In contrast, structured child-focused activities require that an adult caregiver provides the learning opportunities and structured teaching situations, e.g., teaching a child how to insert wooden blocks of different shapes into a box with openings that match these shapes. Parents in Western cultures who are more likely to provide child-focused activities are also more likely to provide a daily schedule for their infants and young children with fixed times for sleeping, napping, and eating, and more opportunities for dyadic one-on-one interactions (Leyendecker et al, 1995). In contrast, children in non-Western cultures are more likely to participate in shared activities with the members of their community, their daily schedule is likely to be centered around an individualized schedule, and they are likely to have more opportunities for interactions with multiple members of their family and other people who make up their daily social environment (Leyendecker et al, 1995;Rogoff, 2003).…”
Section: Culture Matters In Human Developmentmentioning
confidence: 98%
“…Parents in Western cultures who are more likely to provide child-focused activities are also more likely to provide a daily schedule for their infants and young children with fixed times for sleeping, napping, and eating, and more opportunities for dyadic one-on-one interactions (Leyendecker et al, 1995). In contrast, children in non-Western cultures are more likely to participate in shared activities with the members of their community, their daily schedule is likely to be centered around an individualized schedule, and they are likely to have more opportunities for interactions with multiple members of their family and other people who make up their daily social environment (Leyendecker et al, 1995;Rogoff, 2003). All developmental niches include participation in adult activities, guided participation, and specialized child-focused activities, yet the likelihood that children are presented with these different learning opportunities is likely to vary across developmental niches.…”
Section: Culture Matters In Human Developmentmentioning
confidence: 98%